Peran Mediasi Customer Satisfaction pada Hubungan Antara Perceived Value dan Service Quality Terhadap Repurchase Intention - Karnawati, Tin Agustina; Fitrian, Ifan (Jurnal Optimalisasi, 2025)
In the modern era, consumers prioritize convenience and speed in shopping, making drive-thru services an innovative solution to meet this demand. To retain customers, Customer Satisfaction is the key to winning the competition. This study aims to examine the relationships between variables influencing Customer Satisfaction and their impact on Repurchase Intention. The research variables include Perceived Value (X1) and Service Quality (X2) as independent variables, Repurchase Intention (Y) as the dependent variable, and Customer Satisfaction (Z) as the mediating variable. Each variable will be measured by its respective indicators. This research employs a causal research design with a quantitative approach, utilizing primary data collected from 160 respondents via accidental sampling. Data analysis was performed using the SEM-PLS method. The results show that Perceived Value and Service Quality have a significant positive effect on Repurchase Intention. Perceived Value has a positive but not significant effect on Customer Satisfaction, while Service Quality has a positive effect on Customer Satisfaction. Customer Satisfaction mediates the indirect effect of Service Quality on Repurchase Intention but does not mediate the effect of Perceived Value on Repurchase Intention.